Yasynetska Natalia. Semi-calques of English neologisms in the Ukrainian language - Yasynetska Natalia (Philological Treatises, 2020)
The article focuses on the approaches to defining and researching semi-calques (half-loans). The study distinguishes between different types of semi-calques and considers semi-calques of English neologisms of various structure and origin of 1990-2000 in the Ukrainian language.